Violência e conselho municipal da pessoa idosa: fluxo de denúncias e perspectiva instersetorial - Bíscaro, Maria Eduarda Bassan (Universidade Federal de São Carlos, 2023)
Reports of violence against the elderly are a challenge faced by aging populations. Faced with this, various bodies and services are responsible for guaranteeing the rights to a full life, including the Councils for the Rights of the Elderly. Objective: To systematize the flow of complaints received by a Municipal Council for the Elderly (CMI) and identify the sectors involved in following up complaints. Methodology: This is an exploratory, descriptive study based on qualitative and quantitative research. Thematic content analysis was applied based on the theoretical framework. Authorization for the research was obtained. This study had two stages: a literature review and documentary analysis of CMI records relating to complaints received between 2019-2022. Both stages were carried out virtually and a field script was used. Results: Scientific production is scarce, and the six productions identified indicate the theme related to health care measures, and none related to the application of flowcharts in this context. Regarding stage two, it was found that the CMI has documents for registering complaints, but does not have systematized internal flows, nor does it have a flowchart. It primarily receives complaints from the Women's Police Station and Dial 100. It sends most complaints to the Specialized Social Assistance Reference Centre and the main communication channel is through the electronic system (e-mail). This study produced two flowcharts, the first of which was faithful to all the organized collection and the second is a proposal for the CMI, integrating the theoretical content on the subject and identifying the areas of activity and services linked to resolving situations of violence against the elderly. It is hoped that the flowchart will contribute to work processes, agility, and resolution.
Violence and the municipal council for the elderly: flow of complaints and intersectoral perspectiva
Keywords: Gerontologia; Violência contra a pessoa idosa; Conselho; Fluxograma; Assistência à saúde do idoso; Assistência social para idoso; CIENCIAS DA SAUDE; CIENCIAS SOCIAIS APLICADAS; CIENCIAS SOCIAIS APLICADAS::DIREITO::DIREITO PUBLICO; OUTROS::CIENCIAS; OUTROS